1963. Peripartum Outcomes Associated With COVID-19 Vaccination during Pregnancy: A Systematic Review and Meta-analysis. (15th December 2022) - Watanabe, Atsuyuki; Yasuhara, Jun; Iwagami, Masao; Miyamoto, Yoshihisa; Yamada, Yuji; Suzuki, Yukio; Takagi, Hisato; Kuno, Toshiki
Abstract: Background: The risk and benefits of coronavirus disease 2019 (COVID-19) vaccination during pregnancy are under investigation. Pooled evidence regarding neonatal and maternal outcomes in relation to COVID-19 vaccination during pregnancy is scarce. Methods: We searched PubMed and EMBASE databases in April 2022 without language restrictions. We included Prospective trials and observational studies comparing the women who received at least one COVID-19 vaccination during pregnancy with those who did not and reporting neonatal outcomes. Two independent investigators extracted relevant data from each study. Odds ratios (ORs) were calculated using random-effects models. This study followed the Preferred Reporting Items for Systematic Reviews and Meta-analysis guidelines. The primary outcomes were the neonatal outcomes, including preterm birth, small-for-gestational-age (SGA), low Apgar score (< 7 at 5 min), neonatal intensive care units (NICU) admission, and intrauterine fetal death (IFD). The secondary outcomes were maternal outcomes, including maternal SARS-CoV-2 infection, cesarean delivery, postpartum hemorrhage, and chorioamnionitis. Results: Nine observational studies involving 81, 349 vaccinated (mean age, 32.0±4.6 years) and 255, 346 unvaccinated women during pregnancy (mean age, 30.5±5.1 years) were included. COVID-19 vaccination during pregnancy was associated with lower risk of NICU admission (OR, 0.88; 95% confidence intervals [CI], 0.80-0.97) and IFD (OR, 0.73; 95% CI, 0.57-0.94), whereas it was not associated with preterm birth (OR, 0.89; 95% CI, 0.76-1.04), SGA (OR, 0.99; 95% CI, 0.94-1.04), and low Apgar score (OR, 0.94; 95% CI, 0.87-1.02). COVID-19 vaccination during pregnancy was associated with a lower risk of maternal SARS-CoV-2 infection (OR, 0.46; 95% CI, 0.22-0.93), but not associated with increased risk of cesarean delivery (OR, 1.05; 95% CI, 0.93-1.20), postpartum hemorrhage (OR, 0.95; 95% CI, 0.83-1.07), and chorioamnionitis (OR, 0.95; 95% CI, 0.83-1.07). Flowchart of study selection Forest plots showing the odds ratio of neonatal outcomes a: neonatal intensive care units admission, b: intrauterine fetal death, c: preterm birth, d: small for gestational age, e: low Apgar score Forest plots showing the odds ratio of maternal outcomes a: maternal SARS-CoV-2 infection, b: cesarean delivery, c: postpartum hemorrhage, d: chorioamnionitis Conclusion: COVID-19 vaccination during pregnancy did not increase the risk of peripartum outcomes but decreased the risk of NICU admission, IFD, and maternal COVID-19 infection. COVID-19 vaccination should be encouraged for pregnant women. Disclosures: All Authors : No reported disclosures.